Tax Base Estimation of Income – The Proposal of Selected Changes - Witczak, Radosław (Journal of Finance and Financial Law, 2025)
The purpose of the article. One of the measures to combat tax fraud is estimation of the tax base. The provisions point out the reasons and rules of estimating of the tax base. Polish legislation provides tax authorities with a list of six tax base estimation methods they can use. In cases when none of these methods is applicable, tax authorities may use other methods serving the same purpose, but the law (the Tax Ordinance Act) does not indicate what these methods should be. The aim of the article is to propose the changes to the tax base estimation in the Tax Ordinance Act. Methodology. The descriptive study including critical attitude to the legal acts and literature was used to solve the research problem. Results of the research. It would be advisable to introduce legislative changes such as: specifying estimation methods in the regulation, applying the production method, amending regulations regarding exemptions from estimating the tax base, using the method of determining income based on incurred expenses versus undisclosed sources of income, procedural changes.The legislative forms of change were discussed.